If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3bc = 12 + 9bc Solving 3bc = 12 + 9bc Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-9bc' to each side of the equation. 3bc + -9bc = 12 + 9bc + -9bc Combine like terms: 3bc + -9bc = -6bc -6bc = 12 + 9bc + -9bc Combine like terms: 9bc + -9bc = 0 -6bc = 12 + 0 -6bc = 12 Divide each side by '-6c'. b = -2c-1 Simplifying b = -2c-1
| s+808=57 | | -(7-4x)=7 | | 114=2u | | f29=7 | | 11x+11=4x+158 | | 42+5x=9-8x | | v+66=993 | | 6*8=0 | | 284-7x=38x+24 | | 7x+2x-3=5x+9 | | q+407=73 | | -19x-21=35-x | | xy=29 | | 20x^2+60x+45=0 | | q+ -407= -73 | | 3x+1=6x-2 | | r+450=996 | | 4-x=15 | | d-732=-485 | | 630-7x=3x | | 3x+69=8x+12 | | 2+(x-7)+1=7 | | -28-7=10x+23 | | x^6=1.4 | | 2+(x-3)+1=7 | | 35=7d | | 11-t=21 | | 40x^2+20x=0 | | 11=m+6 | | 125=20y-5(15-y) | | 370=m-72 | | c+c+2+c+4+c+6=(c+c+2)+10 |